ANALYSIS FEASIBILITY OF EFFORT BREEDING LAYING HENS - Dermawan, Rizky (Jambura Journal of Animal Science, 2018)
This research aims to know analysis feasibility of effort breeding laying hensof business the cattle laying hens UD. Rizky Layer. The results of this research show the costs that are used on a chicken farm race laying UD Rizky layer of Rp 6,088,941,0/2thn and profit of Rp 1.954.548.670/24Bln of the total population 12,000 tail, the value of R/C Ratio amounting to 1,32 (1,32 > 1), the value of BEP production 5,360.44, the value of BEP costs/acceptance of 1,048,777,173.91, and the value of the BEP cost price/Unit of 36,380.20. This shows the farm UD. Rizky Layer remain eligible to run.